2019
DOI: 10.21037/tlcr.2019.03.14
|View full text |Cite
|
Sign up to set email alerts
|

The impact of epidermal growth factor receptor mutations on the prognosis of resected non-small cell lung cancer: a meta-analysis of literatures

Abstract: Background: Epidermal growth factor receptor (EGFR) mutation represents a good response to EGFRtyrosine kinase inhibitor and an advantageous prognostic factor in advanced-stage non-small cell lung cancer (NSCLC). However, the predictive value of EGFR mutation for prognosis in NSCLC patients after complete surgery, which more reflective of natural process, remains controversial. We sought to examine the predictive value of EGFR mutation in NSCLC. Several studies with small sample sizes have been reported but sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 47 publications
(54 reference statements)
1
19
0
Order By: Relevance
“…Our analysis adds knowledge to existing evidence of survival bene ts in EGFR mutation-positive NSCLC patients. A previous metaanalysis of 19 published studies concluded that EGFR mutation itself was not a prognostic indicator, based on their nding of similar post-operative disease free survival in resected NSCLC patients 22 . Yet, in advanced stage patients who were treated with EGFR-TKIs, EGFR mutation was predictive for progression free survival 13 , implying that the survival bene ts are attributable to treatment following the detection of EGFR mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis adds knowledge to existing evidence of survival bene ts in EGFR mutation-positive NSCLC patients. A previous metaanalysis of 19 published studies concluded that EGFR mutation itself was not a prognostic indicator, based on their nding of similar post-operative disease free survival in resected NSCLC patients 22 . Yet, in advanced stage patients who were treated with EGFR-TKIs, EGFR mutation was predictive for progression free survival 13 , implying that the survival bene ts are attributable to treatment following the detection of EGFR mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The role of oncogenic drivers in the prognosis of resected eNSCLC is debated. Two studies comparing completely resected stage I and I-III NSCLC failed to find differences in DFS and OS between EGFR-wild type (EGFRwt) and EGFR-mutant (EGFRmt) patients (49,50). Similarly, ALK positivity did not predict tumour recurrence after surgery in two retrospective studies (51,52).…”
Section: Adjuvant Icismentioning
confidence: 99%
“…Non-small-cell lung cancer (NSCLC) is the major type of lung cancer, among which, approximately 25% are diagnosed with early-stage NSCLC and are supposed to undergo surgical resection (1,2). However, the high postoperative recurrence rate has a negative impact on prognosis, with approximately 30% for stage I patients and up to 75% for stage III patients (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%